Numerical Analysis of the Factors Affecting the Anti-Slide Pile Design - TANG, Yi; XIE, Qiang; GOU, Wenjin; WAN, Renfeng; LI, Liang (Engineering Transactions, 2017)
The use of anti-slide piles is one of the most important landslide remediation methods, and it is widely used in practical engineering. Anti-slide pile design elements include pile plane position and spacing, the anchorage depth, and pile cross-sectional shape and size. With the displacement of an anti-slide pile head as the evaluation index of the anti-sliding effect of anti-slide pile, ANSYS was used to establish models for numerical simulation to provide analysis of the pile spacing and to determine the anchoring depth and cross- sectional dimensions of the impact of pile top displacement. Using the control variable method, the influence trends and the degree of influence of three factors on the displacement of pile top were studied. Through this analysis, we found that the influence of the pile cross-section size change on the maximum displacement of the pile head is relatively weak, whereas the anchoring depth and pile spacing have a greater impact on the changes in the maximum displacement of the pile; there is a limit of the design parameters, beyond which improvement in the design value is not obvious regarding the limiting of the displacement of the pile top. Further study could investigate the choice of design parameters to optimize the design of anti-slide pile.